2016
DOI: 10.1038/sdata.2016.98
|View full text |Cite
|
Sign up to set email alerts
|

A German-language replication study analysing the role of figurative speech in reasoning

Abstract: According to the metaphorical framing model, the use of metaphors in discussing an issue influences recipients’ understanding and assessment of that issue. In a recent study, participants read a text referring to a city’s crime problem either as a beast or a virus and then proposed counter-measures for that problem. Participants’ suggestions differed depending on the metaphor they had read. This replication matched the original procedure regarding the content of the rhetorical figures (beast vs virus), the top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…They found that even the limited metaphorical information (via a single word) could powerfully influence how people attempted to solve social problems like crime and how they gathered information to make "well-informed" decisions. Christmann and Göhring (2016) replicated Thibodeau and Boroditsky's study (2011) in the German language, concluding that metaphors do indeed frame reasoning. Thibodeau and Boroditsky (2013) further found that the crime is a disease and crime is a wild beast metaphors could influence people's reasoning even when they had a set of options available to compare and select among, which suggests metaphors can influence not just what solution comes to mind first, but also which solution people think is best.…”
Section: Metaphorical Framingsupporting
confidence: 66%
“…They found that even the limited metaphorical information (via a single word) could powerfully influence how people attempted to solve social problems like crime and how they gathered information to make "well-informed" decisions. Christmann and Göhring (2016) replicated Thibodeau and Boroditsky's study (2011) in the German language, concluding that metaphors do indeed frame reasoning. Thibodeau and Boroditsky (2013) further found that the crime is a disease and crime is a wild beast metaphors could influence people's reasoning even when they had a set of options available to compare and select among, which suggests metaphors can influence not just what solution comes to mind first, but also which solution people think is best.…”
Section: Metaphorical Framingsupporting
confidence: 66%
“…In line with previous research on the effects of militaristic metaphors on the endorsement of preventive behaviours (Flusberg et al, 2017;Hauser & Schwarz, 2015;Robins & Mayer, 2000), we want to test whether militaristic metaphors affect emotions, threat perceptions and policy preferences, and whether they shape participants' own thoughts and language choice in the pandemic situation, as shown by previous studies on metaphorical information processing (Christmann & Göhring, 2016;Thibodeau & Boroditsky, 2013).…”
Section: Warfare Metaphors Reasoning and Behaviourmentioning
confidence: 94%
“…And last, we present replication data from Christmann and Göhring 18 , who successfully replicated results of a 2011 paper on the ways in which metaphors can frame reasoning 19 . This data paper stands out because it describes replication data collected in a different language (German) from the one in which the original study was conducted (English).…”
Section: Commentmentioning
confidence: 59%